2011
DOI: 10.1074/jbc.m111.281865
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-assisted Excisive Recombination, a Solitary Role for DnaJ (Hsp40) Chaperone in Lysogeny Escape

Abstract: Background: Site-specific recombination is involved in the temperate phage lysogeny cycle. Results: DnaJ is recruited by a protein specific for excisive recombination. Conclusion: Bona fide chaperone activity of DnaJ enhances prophage excision. Significance: Stress response in E. coli contributes to mobilization of temperate phages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Direct Association of DnaJ and TorI-We have previously shown that DnaJ has the ability to increase the excision efficiency of the KplE1 prophage from the K12 bacterial chromosome (24). The presence of DnaJ increased the affinity of TorI for its specific DNA targets on attL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct Association of DnaJ and TorI-We have previously shown that DnaJ has the ability to increase the excision efficiency of the KplE1 prophage from the K12 bacterial chromosome (24). The presence of DnaJ increased the affinity of TorI for its specific DNA targets on attL.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that DnaJ is also involved in prophage excision of a class of (pro)phages that share very similar recombination modules (24). As this role appeared to be a bona fide chaperone activity of DnaJ, which was independent of DnaK, we have now further characterized the structural features underlying the TorI/DnaJ interaction.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Values represent the average of at least three independent determinations. Alternatively, a PCR amplification was performed on 15 randomly chosen LCB6069 colonies treated or not treated with BCM, using specific primer pairs to test for the presence of attL and attB (44).…”
Section: Methodsmentioning
confidence: 99%